Role of Creatine Kinase in the Troponin Era: A Systematic Review - Daniel Beamish (eScholarship Publishing, University of California, 2021)
Introduction: The diagnosis of non-ST-elevated myocardial infarction (NSTEMI) depends on a combination of history, electrocardiogram, and cardiac biomarkers. The most sensitive and specific biomarkers for cardiac injury are the troponin assays. Many hospitals continue to automatically order less sensitive and less specific biomarkers such as creatine kinase (CK) alongside cardiac troponin (cTn) for workup of patients with chest pain. The objective of this systematic review was to identify whether CK testing is useful in the workup of patients with NSTEMI symptoms. Methods: We undertook a systematic review to ascertain whether CK ordered as part of the workup for NSTEMI was useful in screening patients with cardiac chest pain. The MEDLINE, Embase, and Cochrane databases were searched from January 1995–September 2020. Additional papers were added after consultation with experts. We screened a total of 2,865 papers, of which eight were included in the final analysis. These papers all compared CK and cTn for NSTEMI diagnosis. Results: In each of the eight papers included in the analysis, cTn showed a greater sensitivity and specificity than CK in the diagnosis of NSTEMI. Furthermore, none of the articles published reliable evidence that CK is useful in NSTEMI diagnosis when troponin was negative. Conclusion: There is no evidence to continue to use CK as part of the workup of NSTEMI acute coronary syndrome in undifferentiated chest pain patients. We conclude that CK should not be used to screen patients presenting to the emergency department with chest pain.